1980
DOI: 10.1111/j.1365-2265.1980.tb01021.x
|View full text |Cite
|
Sign up to set email alerts
|

IN VIVO AND IN VITRO STUDIES ON THE EFFECT OF METOCLOPRAMIDE ON ALDOSTERONE SECRETION

Abstract: Metoclopramide, a dopamine antagonist drug, elevated plasma aldosterone and prolactin levels without significantly affecting plasma renin activity, ACTH or potassium. Studies with isolated perfused rat zona glomerulosa cells showed that metoclopramide could directly stimulate aldosterone release and that this action was blocked by dopamine. These results suggest that dopamine may play an important inhibitory role in the control of aldosterone secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 9 publications
1
25
1
Order By: Relevance
“…The changes in PRA following i.c.v. dopamine or metoclopramide administration in the present study are quite different from other reports, 6 l3> l4 in which i.v. administration of dopamine or metoclopramide did not alter the PRA in human subjects.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The changes in PRA following i.c.v. dopamine or metoclopramide administration in the present study are quite different from other reports, 6 l3> l4 in which i.v. administration of dopamine or metoclopramide did not alter the PRA in human subjects.…”
Section: Discussioncontrasting
confidence: 56%
“…Although many investigators have shown that peripherally infused dopamine or metoclopramide alters aldosterone secretion in humans, 3 ' ' 3i l4-M dopamine reportedly had no effect on aldosterone output of bovine adrenal cells, nor did it block the aldosterone response to ANG II in superfused rat adrenal cells. 6 In addition to the present observation, studies on Na-depleted or Na-replete sheep showed that dopamine or metoclopramide had basically no direct effect on the adrenal. 8 ' 10 Furthermore, metoclopramide had no effect on plasma corticosteroid levels in humans, 31314 but it stimulated corticosteroid secretion in sheep.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…From invivo and in-vitro studies, there is indirect evidence that dopamine tonically inhibits aldosterone secretion (2 -I1) and blunts angiotensin II-stimulated aldosterone secretion (31)(32)(33)(34)(35). Two different types of dopaminergic receptors have been identified in the rat adrenal cortex (36): the DA2 type, associated with inhibition of adenylate cyclase and of aldosterone secretion, and the DA1 type, associated with activation of adenylate cyclase and increased cAMP levels, the physiological roles for which are as yet unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although in recent years the emphasis in pathways to aldosterone secretion has been via stimuli to CYP11B2 transcription, earlier literature showed that many effects, including postural changes and those of dopamine, occur within minutes-namely too fast for a transcriptional response. [34][35][36] Finally, the recognition of NEFM as a selective marker of ZG-like APAs gave us the opportunity for testing whether the ZF-like phenotype might be a consequence of its commonest genotype, namely the KCNJ5 mutation, rather than from arising in ZF cells, where KCNJ5 expression is scarce. The disappearance of NEFM from KCNJ5-transfected cells would favor the first of these alternatives and indeed explain why D1R remains on the surface of ZF-like APA cells.…”
Section: Discussionmentioning
confidence: 99%